THE ORF5 VARIATION OF VIETNAMESE PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME VIRUS STRAINS - Chi Nguyen Quynh Ho; Son Nghia Hoang; Thao Thi Phuong Nguyen; Chung Chinh Doan; Mai Thi Phuong Nguyen; Trinh Huu Le; Hoai Thi Thu Nguyen; Long Thanh Le (Slovenian Veterinary Research, 2017)
Porcine reproductive and respiratory syndrome is a devastating disease that causes heavy losses to the economy and the development of agriculture. In this study, we aimed to assess the genetic variation of the ORF5 gene from 12 Vietnamese porcine reproductive and respiratory syndrome virus (PRRSV) strains. The phylogenetic analysis of the ORF5 sequences of Vietnamese strains and other strains indicated that the Vietnamese strains belong to type II. The Vietnamese strains were also separated into two clusters. Five strains BG/12, TG1/12, TG2/12, TG3/12, and TG4/12 were grouped in cluster 1 with a 98% bootstrap value, while the other seven strains HCM/14, TG5/15, TG6/15, TG7/15, ST1/15, ST2/15, and ST3/15 belonged to cluster 2. The alignment of the deduced amino acid sequences demonstrated that the identity between Vietnamese strains with CH-1a, JXA1, and VR2332 strains were 87–93%, 91–98%, and 83–89%, respectively. The mutation of the N21 glycosylation site (N→S) of the GP5 sequence was observed in five Vietnamese strains from cluster 1. The core sequence of the neutralizing epitopes (including five positions at H25, Q27, I29, Y30, and N31) in GP5 was presented in all Vietnamese strains except strain TG1/12. The hydrophobicity plots of GP5 revealed two different positions of BG/12 strain from CH-1a strain and VR2332 strain. The first difference was the missing of a hydrophilic peak from position amino acid 85 to 95. In this region, the CH-1a and VR2332 strains have 3 hydrophilic peaks. The second difference was the loss of another hydrophilic peak at position amino acid 100.